Does the problem begin at the beginning? Medical students’ knowledge and beliefs regarding antibiotics and resistance: a systematic review - Natalia Nogueira-Uzal; Maruxa Zapata-Cachafeiro; Olalla Vázquez-Cancela; Ana López-Durán; Maria T. Herdeiro; Adolfo Figueiras (Antimicrobial Resistance and Infection Control, 2020)
Abstract Background Studies have detected that prescribers display gaps in knowledge and inappropriate attitudes regarding antibiotics and resistances, but it is not known whether these are generated during professional practice or derive from the undergraduate stage of their education. Accordingly, the aim of this study was to identify medical students’ knowledge, beliefs and attitudes regarding antibiotic use and antibiotic resistance, and whether these change over the course of their time at medical school. Methods We conducted a search of the MEDLINE and EMBASE databases, and included studies that measured knowledge and/or beliefs and/or attitudes regarding antibiotic prescribing and/or resistance, among medical students. Results Of the 509 studies retrieved, 22 met the inclusion criteria. While medical students perceived resistance as posing a major public health problem, both worldwide and in their own countries, students in the last two course years were more aware of overprescription of antibiotics in general, and of broad-spectrum antibiotics, at their teaching hospital. There was a considerable lack of knowledge about the treatment of high-incidence infections, and upper respiratory tract infections in particular (41–69% of participants believed antibiotics to be useful for treating these), without any differences by course year. Students were conscious of their personal shortcomings and thus showed willing to improve their education. Conclusions Future physicians display important gaps in knowledge, particularly in terms of treatment of high-incidence infections. This finding may be of use when it comes to designing more effective training in antibiotic stewardship for undergraduates.